PENDAMPINGAN PEMBELAJARAN INKLUSIVISME AGAMA DALAM AL-QUR’AN PERSPEKTIF NURCHOLIS MADJID DI YAYASAN BALQIS - M. Suaib Tahir; Reny Puspita Sari; Jun Firmansyah; Mulyani Mulyani; Wahid Syafrudin (MADANI Abdimas : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
This research aims to explore the concept of religious inclusivism in the Qur'an from the perspective of Nurcholish Madjid. Using a qualitative methodology focusing on textual analysis and interpretation, this study examines Madjid's views on how the Qur'an can be read as a text that supports religious inclusivism. The findings of this study indicate that Madjid interprets several verses of the Qur'an as the basis for religious inclusivism in Islam, emphasizing concepts such as ta'aruf (knowing each other) and ummatan wasatan (middle nation) as key principles. Madjid argues that the Qur'an not only recognizes the existence of other religions but also encourages dialogue and tolerance among followers of different faiths. This research makes a significant contribution to the understanding of religious inclusivism in Islam, especially in the diverse context of Indonesia. This research also highlights the relevance of Nurcholish Madjid's thought in bridging the gap between traditional Islamic values and the challenges of modernity, and offering an alternative perspective to exclusive interpretations of the Qur'an